Klimatanpassning av bebyggelse: En redogörelse av kommunernas förutsättningar att vidta åtgärder för klimatanpassning av bebyggelse i svensk rätt - Asplund Lövgren,Simon (2018)
Climate change and its consequences have long been viewed as one of the defining challenges of our time. The focus of research pertaining to climate change have until recently been overwhelmingly focused on the issue of mitigation while adaptation to climate change has received comparatively little attention. But, as the realization has dawned that many consequences of climate change are already being felt around the world, or are otherwise unavoidable at this stage, focus is increasingly being directed towards the question of climate change adaptation. In Sweden the need for climate change adaptation has been the subject of several state public reports and a few changes in legislation. By studying what conditions are set forth by parts of the Swedish legislation for the adaption of physical development to climate change by the Swedish municipalities this essay strives to contribute to the understanding of whether Swedish legislation may be considered suitable for facilitating a number of necessary adaptation measures. To this end the essay utilizes a legal dogmatic method to interpret the meaning of the law and then evaluates the findings by considering to what extent they respond to the need for adaptation. The conclusion is drawn that the studied legislation, at least in theory, offers a range of possibilities for the Swedish municipalities to consider climate change in the planning of new development but that these are largely facultative or otherwise vaguely defined. In relation to older development on the other hand these possibilities are much more restricted or largely undefined in the legislation.
Keywords: förvaltningsrätt; kommunalrätt; klimatanpassning